Disease interactions in cattle and sheep in northern Cote d'Ivoire - Coulibaly, L.; Diarrassouba, I.; D'Ieteren, G.D.M.; Hecker, P.; Itty, P.; Maehl, J.H.H.; Mahamat, B.; Nagda, S.M.; Paling, R.W.; Rarieya, J.M.; Schuetterle, A.; Thorpe, W.R.; et al. (ILCA/ILRAD, 1988)
Discusses disease interactions in cattle and sheep in northern Cote d'Ivoire. Presents and discusses prevalence of anaemia - producing parasites, prevalence of strongyle egy burdens, PCV infected or uninfected with trypanosomes in the prescence or ascence of internal/blood parasites, PCV during gestation and lactation and weight change during lactation for classes of parasite infection, PCV and daily liveweight change and weaning weight of lambs for classes of parasite infection, and PCV and daily liveweight gain for trypanosome, storngyle egg burden and coccidia classes of young cattle.